FROM KINETIC VIOLENCE TO DIGITAL FEAR: PARADIGM SHIFTS IN NATIONAL LEGAL RESPONSES TO CYBERTERRORISM IN INDONESIA AND UNITED STATES - Nadiah Khaeriah Kadir; Judhariksawan J; Syamsuddin Muhammad Noor; Maskun M.; Imelda Hermilinda Abas (Jurnal Al-Dustur, 2026)
The evolution of terrorism from conventional physical violence to the mass production of digital fear has redefined cyberspace as a critical arena for contemporary security threats. Cyberterrorism, characterized by borderless operations and transnational impacts, poses profound challenges to national legal systems that remain predominantly grounded in territorial sovereignty paradigms. This article aims to analyze the reorientation of national legal frameworks in response to the qualitative shift from traditional counterterrorism models toward regulatory architectures capable of addressing digital disruption. Utilizing a normative-doctrinal legal research method with a comparative approach between Indonesia and the United States, this study evaluates the coherence, adequacy, and effectiveness of national cyber regulations in confronting transnational threats. The findings reveal a significant divergence in legal approaches. the United States has integrated the effects doctrine and the protective principle to extend extraterritorial jurisdiction, whereas the Indonesian legal landscape remains sectoral and fragmented, resulting in enforcement lacunae and conceptual ambiguity. This study asserts that regulatory disparities and the absence of a harmonized statutory definition undermine cross-border cooperation and international legal certainty. The novelty of this research lies in its reframing of cyberterrorism as a qualitative transformation—shifting from acts of physical violence to the generation of digital fear—and offers insights for transitioning toward a more cohesive, technologically neutral legal model.